Electronics in Management - Hertz, David B. (Management Science, 1965)
Since the end of World War II, the single most outstanding development in the world of business has been the economic renaissance of the Free World. From the devastation and dislocation left by 6 years of war, the Western business community has rebuilt and redirected itself in two decades of unparalleled growth and prosperity. The postwar prophets of gloom, who prognosticated postwar collapse and stagnation as in the Great Depression of the 1930s have long since been routed. And a serious economic setback appears now to be less likely than ever. Certainly the business manager of today can look back proudly on a job well done. Clearly this period has been a triumph for the free enterprise system and the traditional concepts and techniques of management. Nevertheless, the business managers of today cannot rest on these accomplishments. For change is in the air, and the traditional concepts of management cannot fully meet the challenge that it brings. These established concepts, of course, themselves originally evolved as new responses to new business challenges. And it is worth remembering that many of the familiar management techniques of today were not traditional concepts 20 years ago. The manager of 1946 would be very uncomfortable and unsure of himself in the sophisticated management world of today. New tools and techniques of management are taken for granted by today's manager. And the search for newer and better techniques presses on.